STRUCTURAL CONTENT OF AN ESP TEXTBOOKS FOR THE STUDENTS IN NON-PHILOLOGICAL INSTITUTES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article deals with the analyze of structural content of an ESP textbook intended for the students of Tashkent chemical-technological institute. In the article, the main attention is paid to the examples of speaking tasks. Topics chosen on each unit are based on actual problems and subjects.